Right Intention and Causation: Reflection on Three Jtaka Tales - Kandel, Tika Ram; Shakya, Sabina (Madhyabindu Journal, 2023)
The focus of this study lies on the right intention (SamyakSaṃkalpa), renunciation of craving, and causation of Karmic fruits (phala) in one’s life relating to the chosen tales from the Jātaka. It is one action which helps in liberating oneself from acquiring what one desires because of one’s cravings, even though it’s result is harmful. It highlights the significance of one’s karma for changing the current plight bringing references from the selected Jātaka tales. Such a study may help to some extent to counter the tag imposed to Buddhism as pessimistic and even nihilistic philosophy. The research approach adopted for this study includes the observation of Buddhist notion of right intention and causation of karma in three Jātakatales. The study finds that the conscious effort for benevolence purpose changes the destiny of people as reflected to Jātakatales. It also adds renunciation in Buddhism that advocates for the Philanthropic works for common benefits. The study concludes that Jātaka tales are enriched with the idea of hard effort for shaping one’s life challenging extraterrestrial or supernatural power.